Answer

Verified

450.3k+ views

Hint: - Here we choose three sides from n sides of a polygon by method of selection to form the triangle i.e.${}^n{C_3}$.Then similarly do for the n+1 sides of the polygon. After that apply the condition of the question.

Complete step by step solution:

Given that,

${T_{n + 1}} - {T_n} = 21$

${T_{n + 1}}$ Can be written as ${}^{n + 1}{C_3}$

$ \Rightarrow {}^{(n + 1)}{C_3} - {}^n{C_3} = 21$

$ \Rightarrow {}^n{C_2} + {}^n{C_3} - {}^n{C_3} = 21$

$\because $ We know that ${}^{(n + 1)}{C_r} = {}^n{C_{r - 1}} + {}^n{C_r}$

$ \Rightarrow \dfrac{{n!}}{{2!\left( {n - 2} \right)!}} = 21$

$\because $We know that ${}^n{C_r} = \dfrac{{n!}}{{r!\left( {n - r} \right)!}}$

$ \Rightarrow \dfrac{{n \times (n - 1) \times (n - 2)!}}{{2 \times (n - 2)!}} = 21$

$

\Rightarrow {n^2} - n = 42 \\

\Rightarrow {n^2} - n - 42 = 0 \\

\Rightarrow {n^2} - 7n + 6n - 42 = 0 \\

\Rightarrow n(n - 7) + 6(n - 7) = 0 \\

\Rightarrow (n - 7)(n + 6) = 0 \\

$

$\therefore $ n=7 0r n=-6

We know that sides cannot be negative $\therefore n = 7$ is the required answer.

Hence, option B is the correct answer.

Note:-Whenever we face such a type of question the key concepts for solving the question is that you have to first choose the three sides from the n sides by selection method to form the triangle and then proceed according to the condition which is given in the question.

Complete step by step solution:

Given that,

${T_{n + 1}} - {T_n} = 21$

${T_{n + 1}}$ Can be written as ${}^{n + 1}{C_3}$

$ \Rightarrow {}^{(n + 1)}{C_3} - {}^n{C_3} = 21$

$ \Rightarrow {}^n{C_2} + {}^n{C_3} - {}^n{C_3} = 21$

$\because $ We know that ${}^{(n + 1)}{C_r} = {}^n{C_{r - 1}} + {}^n{C_r}$

$ \Rightarrow \dfrac{{n!}}{{2!\left( {n - 2} \right)!}} = 21$

$\because $We know that ${}^n{C_r} = \dfrac{{n!}}{{r!\left( {n - r} \right)!}}$

$ \Rightarrow \dfrac{{n \times (n - 1) \times (n - 2)!}}{{2 \times (n - 2)!}} = 21$

$

\Rightarrow {n^2} - n = 42 \\

\Rightarrow {n^2} - n - 42 = 0 \\

\Rightarrow {n^2} - 7n + 6n - 42 = 0 \\

\Rightarrow n(n - 7) + 6(n - 7) = 0 \\

\Rightarrow (n - 7)(n + 6) = 0 \\

$

$\therefore $ n=7 0r n=-6

We know that sides cannot be negative $\therefore n = 7$ is the required answer.

Hence, option B is the correct answer.

Note:-Whenever we face such a type of question the key concepts for solving the question is that you have to first choose the three sides from the n sides by selection method to form the triangle and then proceed according to the condition which is given in the question.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Establish a relation between electric current and drift class 12 physics CBSE

Guru Purnima speech in English in 100 words class 7 english CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Copper is not used as potentiometer wire because class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE